THE CORRELATION BETWEEN DEPRESSION LEVEL AND INDEPENDENT LEVEL IN ACTIVITY OF DAILY LIVING (ADL) IN THE ELDERLY WITH AGE 60 YEARS AND OLDER - HERI TRIWIBOWO (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Depression is a feeling of sadness and pessimism associated with an affliction. It can be an attack is shown on self or a deep feeling of anger that can affect the activity of daily living in the elderly. The purpose of this research was to determine the Relationship between Depression Level and Independent Level in Activity of Daily Living (ADL) in The Elderly with Age 60 Years and Older in Hamlet Candisari Village Awang Awang District Mojosari-Mojokerto. This research used analytic correlation survey method with cross sectional approach. The population in this research were all elderly with age 60 years and older in Hamlet Candisari Village Awang Awang District Mojosari-Mojokerto as many as 89 elderly that were taken by total sampling method. In this research, the data collection methods used a depression questionnaire and standard self-sufficiency measure in ADL. The result of the research were more than half of respondents had mild depression as many as 65 respondents (73.0%) with medium dependency as many as 34 respondents (38.2%), then the respondents of moderate to severe depression as many as 18 respondents (20.3%) respondents with moderate dependence as many as 11 respondents (12.4%), and the respondents who are not depressed as many as 6 respondents (6.7%) can still be independent as many as 3 respondents (3.4%). The analysis used cross tabulation showed the relationship between depression level and independent level in activity of daily living (ADL) the wigher level of depression in elderly, then the lower the level of independence.Elderly should be able to  Activity of Daily Living (ADL) and regularly attend the elderly health post (Posyandu) and interact socially with the surrounding community.